Analysis of Flash Temperature Characteristic of the Roller Enveloping End Face Engagement Worm Drive - Xiaolong Wang (Jixie chuandong)
In order to improve the scuffing load capacity and study the flash temperature of roller enveloping end face engagement worm drive， the mathematical model of friction coefficient between end face worm gear and roller gear under elastohydrodynamic lubrication is established based on tribology and meshing theory of roller enveloping end face engagement worm drive. The time-varying law of friction coefficient is analyzed in the meshing process. On this basis， the calculation model of flash temperature of roller enveloping end face worm drive under elastohydrodynamic lubrication is built based on tribology principle and Block flash temperature theory. The distribution of flash temperature of roller enveloping end face engagement worm drive is analyzed by using Matlab software from mesh in to mesh out. And the input power， lube oil viscosity， roller radius and orifice coefficient， which impacted the flash temperature of this transmission pair are analyzed. The numerical example shows that the input power and lube oil viscosity should not too bigger， roller radius and orifice coefficient should not too smaller，for effectively improving the scuffing strength of the roller enveloping end face engagement worm drive．The research result is very significant for the study of scuffing strength and thermal stress analysis of roller enveloping end face engagement worm drive.